Aristolochic acid I aggravates renal injury by activating the C3a/C3aR complement system. (15th September 2019) - Ye, Jing; Qian, Zhizhi; Xue, Mei; Liu, Yamin; Zhu, Sirui; Li, Yu; Liu, Xiaoli; Cai, Danhong; Rui, Jia; Zhang, Liang
Graphical abstract: Highlights: Aristolochic acid I activates C3a/C3aR system in aristolochic acid nephropathy. C3a/C3aR system functions as a promoter in Aristolochic acid I induced EMT. Antagonist of C3aR reverses the process of fibrosis caused by Aristolochic acid I. Abstract: Previous studies have reported that the complement system is unconventionally activated in many kinds of glomerulonephritis. Multiple complement components participate in the pathogenic process by triggering immune response or other intracellular signaling pathways. Here, we have investigated the role of C3a and its receptor C3aR in aristolochic acid nephropathy (AAN), which, is featured with progressive interstitial fibrosis. Over release of C3a and increased expression of C3aR parallels to the up-regulation of α-SMA and TGF-β1 in AAN, which appeared to promote epithelial-mesenchymal-transition (EMT). To identify the role of complement activation in AAN, we used an inhibitor of C3aR (C3aRA) to block the coupling of C3a to its receptor. Our results confirmed from decreased EMT, the protective effect of C3aRA in cell apoptosis and inflammatory response induced by aristolochic acid I. These results showed that C3a and its receptor C3aR played pathogenic roles in AAN, and renal tubular epithelial cells were potentially pivotal targets of complement activation that could cause pro-fibrotic effects.